The Mediating Role of Employee Coaching Relationship in the Effect of Psychological Empowerment on Organizational Agility (Third Sector Social Economic Review, 2025)
The aim of this study is to examine the mediating role of employee coaching relationship in the effect of psychological empowerment on organizational agility. Within the scope of the research, data obtained from 372 managers working in various sectors were analyzed using SPSS 30.0 and AMOS 25.0 programs. The scales used to measure psychological empowerment (PSG), employee coaching (KCL), and organizational agility (ORC) variables were tested using confirmatory factor analysis (CFA); validity and reliability of the scales were assessed using Cronbach's alpha, composite reliability (CR), and average variance explained (AVE). It was determined that the CFA fit indices of all scales were at acceptable levels, and composite reliability and convergent-divergent validities were achieved. The path analysis created within the framework of structural equation modeling was tested using the bootstrapping method (n=5000), and the fit values of the model were found to be within the tolerance limits (χ2/df = 2.876, CFI = 0.932, RMSEA = 0.0765). According to the analysis results, the psychological empowerment sub-dimensions (meaningfulness, competence, autonomy, and impact) were found to have significant and positive effects on the employee coaching sub-dimensions (relationship authenticity, effective communication, relationship comfort, and development facilitation). Furthermore, all of these intervening variables demonstrated significant effects on organizational agility. In the model, the meaningfulness variable negatively affected organizational agility (β= -0.094, p
Keywords: Psychological Empowerment; Organizational Agility; Employee Coaching Relationship; Organizational Behavior; Agility